2022
DOI: 10.35844/001c.38339
|View full text |Cite
|
Sign up to set email alerts
|

Photo Collages and Near-Peer Interviewing: Scaffolding Data Collection in Youth Participatory Action Research Projects With Children

Abstract: In this brief report, we describe photo collages generated by youth researchers as a photo-elicitation technique in youth participatory action research focused on food (in)security. The approach was implemented with 11 high school students over the course of one semester in an agriscience class at a K-12 alternative school. Student researchers used photo collages as data collection scaffolds within near-peer interviews with elementary students to prompt sharing about food experiences and inequality. This repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…With its roots in Vygotskyan learning theory (Vygotsky, 1987), much of the work on nearpeers has focused on using more experienced peers as instructors, tutors, or mentors, particularly in a medical school setting (Akinla et al, 2018;Bulte et al, 2007;de Menezes & Premnath, 2016) but also in the context of secondary teacher training (Hatch & Grossman, 2009). Recent studies in decoding research (Cameron, 2019;Rouse et al, 2017) and other research on teaching and learning (Baggett et al, 2022;Cook-Sather, 2014) have demonstrated an emerging trend of using near-peers as interviewers. A near-peer interviewer offers the benefit of a reduced power imbalance.…”
Section: Decoding Student Thinking Using Near-peer Interviewsmentioning
confidence: 99%
“…With its roots in Vygotskyan learning theory (Vygotsky, 1987), much of the work on nearpeers has focused on using more experienced peers as instructors, tutors, or mentors, particularly in a medical school setting (Akinla et al, 2018;Bulte et al, 2007;de Menezes & Premnath, 2016) but also in the context of secondary teacher training (Hatch & Grossman, 2009). Recent studies in decoding research (Cameron, 2019;Rouse et al, 2017) and other research on teaching and learning (Baggett et al, 2022;Cook-Sather, 2014) have demonstrated an emerging trend of using near-peers as interviewers. A near-peer interviewer offers the benefit of a reduced power imbalance.…”
Section: Decoding Student Thinking Using Near-peer Interviewsmentioning
confidence: 99%